Canine Atopic Dermatitis - Efficacy of Sublingual Immunotherapy - Choi, Minseok; Yun, Taesik; Lee, Dohee; Koo, Yoonhoi; Chae, Yeon; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Acta Scientiae Veterinariae, 2024)
Background: Canine atopic dermatitis (CAD) is a hereditary pruritic and inflammatory allergic skin disease associated with elevated IgE levels. Although, several treatments for CAD exist, allergen-specific immunotherapy (ASIT) is the only treatment that induces tolerance to pathogenic allergens. Sublingual immunotherapy (SLIT) is effective, convenient, and safe. This case report describes the successful treatment of a bitch with atopic dermatitis using SLIT, emphasizing the efficacy and safety of SLIT as a long-term management strategy for CAD. Case: A 3-year-old spayed female Dachshund presented with non-seasonal chronic pruritus and generalized alopecia. The onset of pruritus occurred at 6 months of age, and its severity, measured by the pruritus visual analog scale, score was 5 out of 10. Dermatological examination revealed alopecia and scales on the dorsum and tail, and alopecia, lichenification, and crust on the medial side of the forelimbs. Diagnostic tests confirmed superficial pyoderma and Malassezia dermatitis. Initial treatment included amoxicillin/clavulanate, itraconazole, and a shampoo containing chlorhexidine gluconate and miconazole nitrate. An elimination diet trial was performed using a commercial diet to diagnose canine adverse food reaction (CAFR). However, 11 days after treatment initiation, the microbial and fungal skin infections and pruritus did not improve. Prednisolone was subsequently prescribed to alleviate pruritus and evaluate the response to glucocorticoids. At 24 days after the administration of prednisolone, pruritus reduction and lesion improvement were observed. Thereafter, prednisolone was tapered to 0.5 mg/kg EOD and discontinued 38 days after the initial administration. After prednisolone discontinuation, cytology did not reveal any cocci or Malassezia sp. Therefore, treatment with amoxicillin/clavulanate and itraconazole was discontinued. Two weeks after the discontinuation of prednisolone, pruritus relapsed, and cytology revealed no infection. The dog was initially treated with oclacitinib and planned to be managed with ASIT following an intradermal skin test at 2 weeks later. A provocative challenge was performed after the pruritus, and the lesions were well managed with oclacitinib. Because the clinical signs did not worsen, CAFR was excluded. The Favrot criteria was used to diagnose CAD by ruling out other skin conditions. An intradermal skin test was performed for 27 allergens, and oclacitinib was administered for SLIT, with allergens showing a positive reaction. After the administration of SLIT and oclacitinib, pruritus was well controlled and no recurrence was observed. At 763 days and 1638 days after the commencement of SLIT, oclacitinib and SLIT were discontinued, respectively. Notably, 9 months after discontinuing SLIT, complete remission of CAD was observed. Discussion: ASIT is used in veterinary medicine to treat CAD. A comprehensive clinical study found that SLIT has a success rate of 55%. The oral mucosa’s low pro-inflammatory cell counts underscores SLIT’s safety. Considering its efficacy and safety, ASIT was initiated with SLIT. ASIT can take > 12 months to improve CAD. Therefore, oclacitinib was prescribed to control pruritus. Complete remission of CAD was confirmed at the time of writing 9 months after SLIT discontinuation. This case indicates that SLIT could be an effective and safe therapeutic option for the long-term management of CAD. Keywords: dogs, canine atopic dermatitis, Immunotherapy, Sublingual immunotherapy